Mãe Iemanjá/ Iemanjás (série de 3 desenhos) / Frame do vídeo "Promessa na praia" - Magalhães, Carla (Das Questões, 2018)
Mãe Iemanjá/ Iemanjás (série de 3 desenhos) / Frame do vídeo "Promessa na praia"